The Analysis of Language Features Used by Male and Female Fitness Influencers in Tiktok Videos - Ida Ayu Fortuna Ningrum; Ni Nyoman Padmadewi; I. G. A. Lokita Purnamika Utami (SOSHUM : Jurnal Sosial dan Humaniora, 2023)
Nowadays, the number of fitness influencers from both genders is rapidly increasing in the fitness industry. Both genders have their language features and characteristics that can be seen in their Tiktok videos. This study aimed to investigate the features and typical characteristics of the language used by Indonesian male and female fitness influencers. This study applied a qualitative descriptive research method by analyzing the video script based on Lakoff’s Theory (1973) and Tennan’s Theory (1990). The findings indicated that male fitness influencers typically speak with greater directness and assertiveness. Also, basic and simple words are mostly used by male influencers. On the contrary, female fitness influencers mostly use extensive vocabulary in their rapport talk. It is intended that this study would serve as the foundation for further investigation related to language gender.